Comparison of Survey Methods in Norovirus Outbreak Investigation, Oregon, USA, 2009 - John Y. Oh; June E. Bancroft; Margaret C. Cunningham; William E. Keene; Sheryl B. Lyss; Paul R. Cieslak; Katrina Hedberg (Emerging Infectious Diseases, 2010)
We compared data from an Internet-based survey and a telephone-based survey during a 2009 norovirus outbreak in Oregon. Survey initiation, timeliness of response, and attack rates were comparable, but participants were less likely to complete Internet questions. Internet-based surveys permit efficient data collection but should be designed to maximize complete responses.